Simple Determination of Elemental Size-distributions of Particulate Matter in Waste Water by Inductively Coupled Plasma Optical Emission Spectrometry - NISHIKAWA, Masataka; TANAKA, Yuka; SAKURAI, Chiaki; AMANO, Yuko; UDAGAWA, Aya (Journal of Environmental Chemistry, 2018)
In waste water treatment, the removal of various trace elements is usually achieved by the addition of inorganic flocculants such as iron chloride. The efficiency of the process depends on the size distribution of the suspended particles formed in the coprecipitation process. In this study, using iron chloride as flocculant, the suspended particles in a waste water sample were subject to successive filtrations by Nucleopore filters (pore size: 10, 5, 3, 1, 0.6, 0.4, 0.2 µm, respectively) and then the total Fe and trace elements in the unfiltered water and the trace elements (including Fe) in each filtrate were measured by inductively coupled plasma optical emission spectrometry（ICP-OES). For verification of the ICP-OES results, particulate Fe concentrations associated with each size fraction were determined after acid decomposition of each filter and analysis of the respective digests by ICP-OES. From examination of the size-distribution curve for the particulate Fe fractions (measured after acid decomposition) with that for Fe determination in the unfiltered sample, it was deduced that Fe particles in the size fractions less than ～ 3 µm were completely atomized in the ICP discharge. The mode diameters of the particulate forms of Fe in the simulated wastewater were approximately 1 µm in the Fe coprecipitation process and 2.5 µm in the Fe-P coprecipitation process. These samples also exhibited the same mode diameters of suspended particles by Coulter counter measurement. In addition, the shapes of the distribution curves by direct ICP-OES measurement were comparable to those by Coulter counter measurement. In conclusion, the combination of direct ICP-OES measurement with sequential filtration using a range of Nucleopore filters represents a powerful scheme for quality control of the coprecipitation/coagulation conditions in wastewater treatment.